Agriculture to Industry: Structural Transformation and the Role of Manufacturing in Jambi’s Economic Growth - Aini, Halia Butra; Puspita, Dwi Darma; Marisa, Feny; Melliny, Vinny Dwi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study examines the role of the manufacturing sector in the economic development of Jambi Province during the period 2007–2024. The research addresses the uncertainty regarding whether the manufacturing sector functions as a base sector and evaluates the extent to which key economic factors contribute to its performance. Using the Location Quotient (LQ) and Dynamic Location Quotient (DLQ) methods, the study identifies the structural dynamics of the sector, while a log-linear regression model is employed to analyze the effects of investment, labor, and the number of business units on the sector’s GRDP. The results indicate that the manufacturing sector remained predominantly non-base throughout the period, with a temporary base status occurring between 2011 and 2020. Regression findings reveal that labor and the number of business units exert positive and significant effects on the manufacturing GRDP, whereas investment shows inconsistent impacts. On average, the manufacturing sector contributed 12.06 percent to Jambi’s total GRDP. These findings highlight the need for strengthened industrial policy strategies focused on enhancing labor capacity, expanding business unit development, and improving investment effectiveness to support regional economic diversification and resilience.